EFEKTIVITAS SISTEM PEMBERIAN INSENTIF DAN PELATIHAN TERHADAP KINERJA KARYAWAN PT. XYZ - YENNY WIDIANTY; SAHAT SINAMBELA (Faktor Exacta, 2012)
Execution giving of employees grounding and incentive represent one of the conservancy of very important employees to maintain employees which with quality. For that, hence PT. XYZ try to maintain its employees which have had ability, membership, loyality and pushing him/ it so that/ to be having high performance through giving of incentive and intensify execution training of employees. Data collecting done with questionayre (enquette). Obtained to be data to be analyzed constructively SPSS version computer 11.5. onclusion 1) Pursuant to result of analysis test regression, especially test F ( test variance) indicating that variable gift of training and incentive by together have influence which is significant to employees performance. PT XY Z, where Fhitung variable value gift of training and incentive to employees performance equal to 62,213 > Ftabel = 3,25 2) Pursuant to result of regression analysis, especially test t indicate that variable influence gift of incentive to employees performance. PT XYZ is positive and significant, where t calculates bigger than t of is tables of 3) from result of analysis test t obtained by training variable influence to PT XYZ employee’s performance is positive and significant, because t value count/calculate bigger than t value of is tables of. Keywords: Incentive, Training, Perfomance